MODERN TECHNOLOGIES AND HUMAN HEALTH (Education in the 21st Century, 2023)
Today's scientific, technical, industrial, economic progress, unprecedented development of IT and an integral component of public life, it seems, should have contributed to the development of civilization and a sharp improvement in the standard of living of mankind. Meanwhile, in reality, on the path of these unprecedented rises and rapid developments, a person has faced a number of problems and challenges that disrupt his life, health, normal life, which deserve attention and require appropriate attitude and solutions.Therefore, it is necessary to find out what role pedagogical valeology plays not only in the upbringing and training of a person, but also in preserving and improving the health of society. To do this, it is necessary to create a stable motivation for health in a person, for the formation of a health culture. And this needs to be formed from preschool age and ensure consistency of theoretical and practical knowledge in the field of general education.At all times, youth and safety are in the spotlight. In general, respect for every person begins with the attitude of society towards the child. A society that loves children takes care of ensuring and preserving their health, creating conditions for full-fledged upbringing, development and manifestation of abilities. Therefore, to resolve and prevent this problem requires a comprehensive approach from all interested structures.Today, the State's recognition of the right to protect children's health, enshrined in various international treaties and declarations, as well as in national legislation, obliges the State to provide adolescents with information and educational services to protect and improve their health. Pedagogical valeology plays an exceptional role in this process, it deals with the issues of education and upbringing of the younger generation aimed at forming a culture of health and a healthy lifestyle, training and the use of modern health technologies, the problems of applying those pedagogical and methodological Arsenal that are significantly aimed at satisfying the physical and spiritual needs of the child, maintaining health, comprehensive personal development in the context of socialization.Moreover, measures aimed at strengthening a healthy lifestyle are the best contribution to general education schools, as well as to the health of the population, and, as a result, have a positive impact on the economic well-being of the country., In order to form responsible behavior, we attach importance to the implementation of targeted, consistent and comprehensive educational work at all levels of the education system. Today, more than ever, in order to ensure the readiness of schoolchildren to lead a healthy lifestyle in each age period, it is necessary to purposefully form requirements and motives that stimulate the possession of knowledge, abilities and skills that will allow them to independently use healthy lifestyle technologies, adequately estimate the role of health in the formation and socialization of personality.